2007
DOI: 10.1007/s11085-007-9085-7
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Temperature Internal Oxidation in Fourth Generation Ru-bearing Single-Crystal Nickel-base Superalloys

Abstract: Fourth-generation, Ru-bearing, Ni-base superalloys offer superior microstructural stability over previous generations, affording greater density-corrected creep strength, but in common with their predecessors, have only borderline ability to form and maintain a protective oxide layer. This is particularly so at intermediate temperatures of around 750°C at which temperature internal oxidation can occur. In this present study, the nature of this attack has been examined in experimental 3 and 5 mass % Ru alloys. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
3
8
0
1
Order By: Relevance
“…Evidence of slow-growing protective spinels has been previously reported [19]. The chromite formed here showed slower growth kinetics than the titanium-doped Cr2O3 formed at bar pressure.…”
Section: Discussionsupporting
confidence: 73%
“…Evidence of slow-growing protective spinels has been previously reported [19]. The chromite formed here showed slower growth kinetics than the titanium-doped Cr2O3 formed at bar pressure.…”
Section: Discussionsupporting
confidence: 73%
“…As discussed elsewhere [13,17], the uncoated Ru-bearing alloys exhibit sub-surface pit formation during oxidation at 750 o C as is shown in Figure 6. The aluminized versions of these alloys show no evidence of such attack at this temperature as can be seen from Figure 7.…”
Section: Characterization Of Oxidesmentioning
confidence: 52%
“…Ru, which is added to fourth generation Ni-base superalloys, would be a good example. The effects of Ru on the oxidation resistance of Ni-base superalloys are still controversial [1,2,25,26,[35][36][37] ; however, some studies [25,26] reported that Ru-containing Ni-base superalloys show inferior oxidation resistance than the previous generation alloys, although Ru provides excellent creep properties and microstructure stability at an elevated temperature. [38,39] A prediction or model of the oxidation behavior, based on alloy composition, should also correspond to such changes.…”
Section: Discussionmentioning
confidence: 99%